A History of Concussion Affects Relevancy-Based Modulation of Cortical Responses to Tactile Stimuli - Adams, Meaghan S.; Niechwiej-Szwedo, Ewa; McIlroy, William E.; Staines, William R. (Frontiers in Integrative Neuroscience, 2020)
Modulating cortical excitability based on a stimulus’ relevance to the task at hand is a component of sensory gating, and serves to protect higher cortical centres from being overwhelmed with irrelevant information (McIlroy et al., 2003; Kumar et al., 2005; Wasaka et al., 2005). This study examined relevancy-based modulation of cortical excitability, and corresponding behavioural responses, in the face of distracting stimuli in participants with and without a history of concussion. Participants were required to make a scaled motor response to the amplitudes of visual and tactile stimuli presented individually or concurrently. Task relevance was manipulated, and stimuli were occasionally presented with irrelevant distractors. Electroencephalography (EEG) and task accuracy data were collected from participants with and without a history of concussion. The somatosensory-evoked N70 event-related potential (ERP) was significantly modulated by task relevance in the control group but not in those with a history of concussion, and there was a significantly greater cost to task accuracy in the concussion history group when relevant stimuli were presented with an irrelevant distractor. This study demonstrated that relevancy-based modulation of electrophysiological responses and behavioural correlates of sensory gating differ in people with and without of a history of concussion, even after patients were symptom-free and considered recovered from their injuries.